2010
DOI: 10.1016/j.jdermsci.2010.07.015
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of protein kinase D inhibitors for prevention/treatment of epidermal tumors

Abstract: Background-The serine/threonine kinase protein kinase D (PKD) has been proposed to be a proproliferative, anti-differentiative signal in epidermal keratinocytes. Indeed, the phorbol ester tumor promoter, 12-O-tetradecanoylphorbol 13-acetate (TPA) induces biphasic PKD activation, which mirrors the biphasic response of initial differentiation followed by proliferation and tumor promotion seen in TPA-treated keratinocytes in vitro and epidermis in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…These results confirm that PKD1 is an anti-differentiative and pro-proliferative signaling enzyme in mouse keratinocytes, similar to human keratinocytes [24], but are unique in that they were obtained with the use of the floxed PKD1 mouse model rather than overexpression [40] or RNA interference [24], with the attendant caveats of these methods. Thus, in this study, we used PKD1-floxed mice that possess loxP sites flanking exons 12 through 14 of the PKD1 gene, which encodes part of the catalytic domain.…”
Section: Discussionsupporting
confidence: 69%
“…These results confirm that PKD1 is an anti-differentiative and pro-proliferative signaling enzyme in mouse keratinocytes, similar to human keratinocytes [24], but are unique in that they were obtained with the use of the floxed PKD1 mouse model rather than overexpression [40] or RNA interference [24], with the attendant caveats of these methods. Thus, in this study, we used PKD1-floxed mice that possess loxP sites flanking exons 12 through 14 of the PKD1 gene, which encodes part of the catalytic domain.…”
Section: Discussionsupporting
confidence: 69%
“…Treatment of keratinocytes with resveratrol induced a dose-dependent increase in transglutaminase activity, while simultaneously inhibiting DNA synthesis, with a half-maximal concentration of 35 μM. Finally, resveratrol and 1, 25(OH) 2 D 3 synergistically increased transglutaminase activity [84]. us, resveratrol inhibits keratinocyte proliferation, while stimulating differentiation.…”
Section: Ratsmentioning
confidence: 87%
“…Lee et al showed that resveratrol increased the expression level and deacetylase activity of SIRT1, resulting in apoptosis [172]. Other studies suggest that resveratrol inhibits DNA synthesis, while increasing transglutaminase activity via inhibition of protein kinase D activity [84]. Moreover, activation of SIRT1 by resveratrol could also increase keratinocyte differentiation [83].…”
Section: Keratinocyte Proliferation and Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our laboratory has also shown that PKD1 co(over)-expression increases the promoter activity for the basal layer marker, keratin 5, and decreases the promoter activity of involucrin, a marker of differentiation [12]. More recently, we found that overexpression of a constitutively active PKD1 construct (in which serines 738 and 742, equivalent to serines 744 and 748 in mouse PKD, are mutated to phosphorylation-mimicking glutamates) increases keratinocyte proliferation and a dominant-negative PKD1 construct (in which serines 738 and 742 are mutated to unphosphorylatable alanines) inhibits growth [13]. Jadali and Ghazizadeh [14] also reported a role for PKD1 in the proliferation observed with reentry of growth-arrested mouse keratinocytes into the cell cycle.…”
mentioning
confidence: 99%